The effect of soil salinity towards the production of paddy yield in 12 Ladang Merdeka under KADA in Kelantan / Mohamad Shahrul Fazli Roslan - Fazli Roslan, Mohamad Shahrul (Faculty of Plantation and Agrotechnology, 2016)
The secondary data has been taken at Lembaga Kemajuan Pertanian Kemubu (KADA) and take soil sampling at 12 area during semester break .The data was analysis using Sigma Plot and Microsoft excel software. Salinity is one of the dominant environmental factors limiting the productivity of crop plants because most of the crop plants are sensitive to salinity caused by high concentrations of salts in the soil, and the area of land affected by it is increasing day by day. Salinity not only decreases the agricultural production of most crops, but also, effects soil physicochemical properties, and ecological balance of the area. The impacts of salinity include low agricultural productivity, low economic returns and soil erosions, Salinity effects are the results of complex interactions among morphological, physiological, and biochemical processes including seed germination, plant growth, and water and nutrient uptake. Salinity affects almost all aspects of plant development including: germination, vegetative growth and reproductive development. Soil salinity imposes ion toxicity, osmotic stress, nutrient deficiency and oxidative stress on plants, and thus limits water uptake from soil